Resolution of Adultery Offenses through the Mbasuh Dusun Mechanism: A Study of Legal Pluralism - Maidani Maidani; Rahmi Hidayati Al Idrusiah; Ruslan Abdul Gani; Muhammad Farhan HR (Journal of Progressive Law and Legal Studies, 2026)
This study examines the resolution of adultery-related offenses through the Mbasuh Dusun mechanism in Muko-Muko Bathin VII District, Bungo Regency, identifies the challenges encountered in its implementation, and analyzes the harmonization of customary law, Islamic law, and national law in the settlement of adultery cases. The research adopts an empirical juridical approach employing a descriptive qualitative method. Data were collected through interviews, field observations, and document analysis involving customary leaders, religious figures, village officials, and members of the local community. The findings indicate that the Mbasuh Dusun mechanism represents a customary law–based dispute-resolution model that emphasizes deliberation, restoration of social equilibrium, and the preservation of communal harmony. The settlement process involves customary institutions, religious leaders, village authorities, offenders’ families, and community representatives in determining forms of resolution perceived as fair and socially acceptable. Major challenges in implementing this mechanism include legal dualism between customary law and national law, social transformation driven by modernization, declining customary legitimacy, and issues concerning the effectiveness of enforcing customary sanctions. The study further reveals that harmonization among customary law, Islamic law, and national law may be developed through a restorative justice framework emphasizing dialogue, offender accountability, restoration of social relationships, and the strengthening of customary institutions. The study contributes that the Mbasuh Dusun mechanism demonstrates the continuing relevance of customary law as a local wisdom–based dispute-resolution instrument within Indonesia’s plural legal system.